Komparasi Penerapan Al-Wasiah Al-Wajibah Mesir dan Indonesia - Hamdi, Ahmad Hilmi (IAI Nasional Laa Roiba Bogor, 2024)
Islamic Family Law in the Muslim world began to reform in the 20th century. Mandatory wills are part of legal reform efforts in the Islamic world, which have now been implemented, especially in Indonesia. However, the results of this reform effort are not completely perfect because there are still many problems related to the distribution of inheritance through mandatory wills. Therefore, Indonesian ulama have reached a consensus regarding the implementation of mandatory wills in the Compilation of Islamic Law (KHI), by adopting and creating from Egyptian law No. 71 of 1946. This research includes qualitative research, the method used in this writing is library research by examining books, articles and literature related to the theme being studied. The obligatory will is a new law implemented by Middle Eastern clerics, namely Egypt, which was then adopted by various other Middle Eastern Islamic countries.